Aspek Hukum Perjanjian Kredit Dengan Agunan Kapal - Agus Riyanto (Jurnal Selat, 2015)
This studyhas the objective toanalyze the data and information regarding the arrangement of credit agreement with collateral vessels in Indonesia. This research is a normative juridical that focus on the legal norms in force which are both contained in the legislation and literature. The method of data analysis was applied by using the model or method qualitative text analysis of the legislation and expert opinions relating to thelegal aspects ofthe loan agreement with collateral vessels. The results showed that, the vessel is possible as collateral in a bank credit agreement. Normatively, there are two ways to do binding guarantee with a form of collateral vessels. The first is the size of mortgagesto 20 m3 vessel with gross tonnage or more, the second is the fiduciary for vessels of under 20 m3 gross tonnage. Keywords : Collateral, Mortgages and Fiduciary